Mucosal snare resection-endoscopic submucosal excavation for gastric submucosal tumors: a retrospective study (with video) - Wei, Wei; Zheng, Xiaolong; Ye, Yongli; Li, Hongxia; Hong, Yiping; Cai, Jianting (Frontiers in Oncology, 2025)
AimsThis study aimed to compare the clinical outcomes of patients with submucosal tumors treated with endoscopic submucosal excavation (ESE) and those treated with mucosal snare resection-endoscopic submucosal excavation (MSR-ESE).MethodsWe retrospectively analyzed clinical data from patients who underwent ESE or MSR-ESE at the Second Affiliated Hospital of Zhejiang University School of Medicine between January 2023 and January 2024. Factors such as operation time, intraoperative perforation, postoperative adverse events, postoperative fasting time, antibiotic use, hospitalization duration, costs, and pathological diagnosis were compared between the two procedures.ResultsA total of 180 patients with submucosal tumors were included in this study. The MSR-ESE group consisted of 75 patients (41.7%), while the ESE group had 105 patients (58.3%). Propensity score matching (PSM) showed no significant differences in postoperative antibiotic use, fasting time, or intraoperative perforation between the two groups (P>0.05). However, the MSR-ESE group demonstrated shorter operation and hospitalization times, lower hospitalization costs, and a reduced incidence of postoperative peritonitis (P<0.05). Multivariate logistic regression analysis identified operation time as an independent risk factor for unplanned intraoperative perforation, with the likelihood of perforation increasing significantly as operation time increased (P=0.007, OR=1.015, 95% CI, 1.004 to 1.026).ConclusionMSR-ESE outperforms ESE with shorter operation times, lower costs, and fewer postoperative complications, making it a safe and effective treatment for gastric submucosal tumors.